Comparison of the exergy efficiency of four power generation systems from methane using fuel cells. Issue 62 (11th August 2017) - Wang, Zhe; Fan, Weiyu; Zhang, Guangqing
Abstract : Exergy analyses on four solid oxide fuel cell (SOFC) systems using methane as the original fuel are conducted. Abstract : Exergy analyses are carried out on four different solid oxide fuel cell (SOFC) systems using methane as the original fuel, with focus on exergy flows, efficiency and destruction. The four processes are (1) CH4 -SOFC, which is a CH4 directly fuelled SOFC system with a CO2 capture unit; (2) CH4 -SOFC-CLC, in which the CH4 -SOFC system is integrated with chemical looping combustion (CLC); (3) SMR-SOFC, i.e. a SOFC system using H2 (H2 -SOFC) generated by steam methane reforming (SMR); (4) MC-SOFC-DCFC, which is a combined system of H2 -SOFC and a direct carbon fuel cell (DCFC) where H2 and C are supplied by methane cracking (MC). Generally, the CH4 -SOFC and CH4 -SOFC-CLC processes which directly use CH4 as the fuel of cells have higher exergy efficiency. MC-SOFC-DCFC reaches an overall exergy efficiency of 71.4%, which is 17% higher than that of SMR-SOFC (54.4%) due to the higher exergy efficiency of MC than SMR. The effects of operating parameters on the performance of CH4 -SOFC are also examined in detail. The results of this investigation demonstrate that the development of methane directly fuelled SOFC, decreasing its operating temperature and suitable capture of CO2 are the key technologies to improve the energy conversion efficiency of methane fuelled SOFC systems.